Effects of nitrogen and potassium on the chemical composition of coffee beans and on beverage quality - Junia Maria Clemente; Herminia Emilia Prieto Martinez; Leonardo Corrêa Alves; Fernando Luíz Finger; Paulo Roberto Cecon (Acta Scientiarum. Agronomy, 2015)
The ratio of nitrogen (N) to potassium (K) is important in the production of specialty coffees because the relative amounts of N and K can either suppress the formation or increase the concentration of compounds that are essential to the flavor and aroma of specialty coffees. The purpose of this study was to evaluate the effect of different N:K ratios (w/w) and K doses on the cup quality of coffee. The concentrations of chemical compounds essentials to achieve good flavor and aroma, the N and K contents, and the caffeine contents of coffee leaves and beans were evaluated in this study. The N:K ratio and the K dose were found to be important factors in cup quality, the best quality corresponding to an N:K ratio of 1:1.56. The best cup quality was obtained from beans with greater PPO activity, caffeine, color index, and sugars and lower total tritatable acidity, pH, electrical conductivity and leached potassium.